2012
DOI: 10.1007/s00384-011-1381-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative blood pressure changes as a risk factor for anastomotic leakage in colorectal surgery

Abstract: PurposeAnastomotic leakage is a serious complication after colorectal surgery. Pre- and intraoperative factors may contribute to failure of colorectal anastomosis. In this study we have tried to determine risk factors for anastomotic leakage, with special emphasis on intraoperative blood pressure changes.MethodsDuring a 24-month period, patients receiving a colorectal anastomosis were prospectively evaluated. For each patient preoperative characteristics, intraoperative adverse events and surgical outcome data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 19 publications
3
28
2
1
Order By: Relevance
“…Post et al . reported that the hypotension caused by intraoperative blood loss increases anastomotic leakage . Our data may support their interpretation because the circulatory dynamics vary between individuals.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Post et al . reported that the hypotension caused by intraoperative blood loss increases anastomotic leakage . Our data may support their interpretation because the circulatory dynamics vary between individuals.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, operative blood loss was significantly correlated to anastomotic leakage. Optimal divergent cut‐off values for operative blood loss influencing short‐ and long‐term outcomes have not been reported, but several authors have reported that operative blood loss is correlated with anastomotic leakage . Therefore, the cut‐off values were varied according to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic leakage is a serious postoperative morbidity that is reported to occur in 3.6% to 6% of patients after colorectal surgery [5][6][7][8][9] , and is associated with prolonged hospital stays, delays in starting postoperative adjuvant therapy, and often requires diverting stoma. Anastomotic leakage also increases the postoperative mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that patients with prolonged diastolic blood pressure drops have a significantly increased risk of anastomotic leak. 113 Interestingly, the method of treating hypotension may be very important. Patients who have postoperative treatment with vasopressors have an over three-to fourfold increase in anastomotic leak rate and the longer the exposure to vasopressors, the higher the risk of anastomotic leak.…”
Section: Hypotensionmentioning
confidence: 99%